DNA damage and health in pregnancy - Furness, D.L.F.; Dekker, G.A.; Roberts, C.T. (Journal of reproductive immunology, 2011)
In healthy pregnancy reactive oxygen species and antioxidants remain in balance and DNA damage is repaired effectively. However, pregnancy is an inflammatory state exhibiting increased susceptibility to oxidative stress such that this balance can be easily disrupted. Increased DNA damage has been shown to be involved in many pathological states including pregnancy complications. Modern lifestyles including exposure to pollutants, poor diet, and lack of exercise cause excess inflammation, oxidative stress, and ultimately DNA damage. There is a growing body of literature providing evidence that these lifestyle changes are increasing our risk of infertility, miscarriage, and late-gestation pregnancy complications. Moreover, baseline DNA damage rises with age and couples in developed societies are delaying childbirth, placing them at further risk. In order to understand the effect of lifestyle and DNA damage on pregnancy health we require large prospective studies, with the collection of samples prior to conception and endpoints of time-to-pregnancy, early pregnancy loss, and late-gestation maternal and fetal health.